Nursing characteristics and patients’ outcomes: a retrospective study - Aung, Khin Thandar; Ghazali, Aini fatimah; Tin, Myo Han (Asian Journal of Medical and Health Research (AJMHR), 2016)
Improving the quality of health care is an increasingly important goal in the National Health Care system. Quality of care can be determined by patients’ outcomes. It is important as an improvement of patients’ outcomes that are related to receiving better health care, improving efficiency of care, cutting down the cost of health expenses and lastly decreasing mortality rate. Pressure ulcers have a detrimental effect on patient health and well-being and as well as medication errors that are placed as an important measurement tool for patients’ outcomes. It is important to identify patients’ outcomes as to differentiate critical thinking and problem solving skills of nurses from different educational and working experience background. The aim of this study was to investigate the nurses’ characteristics and patients’ outcomes in medical and surgical wards. This is a retrospective, descriptive study involving nurses and patients who had been hospitalized in medical and surgical wards at Hospital Tengku Ampuan Afzan (HTAA) Kuantan, Pahang. Nursing characteristics and data would be extracted from existing database within the institution for 1 year of the period to determine patients' outcomes and nursing characteristics. Descriptive statistic and chi-square test using PASW Statistic Version 19.0 were used as data analysis. The results obtained showed that majority of nurses in medical and surgical wards was having diploma (79.2%) and having working experience less than 5 years (62.5%). Meanwhile the total prevalence of Hospitalacquired Pressure Ulcer (HAPU) among non-ambulatory patients in medical and surgical wards was 19.93% and the total prevalence of medication errors in medical and surgical wards was 25.69%. There was no association between non-ambulatory patients and Hospitalacquired Pressure Ulcer (HAPU) (p>0.05). As nurses are important to play central role in providing the best quality of care, the nurse must be provided with an essential knowledge and practice to be able to cure the patients holistically with an ability in planning the correct and appropriate intervention immediately. Keywords: Nursing characteristics, Patients' Outcomes, Pressure ulcers, Medication errors